PENGEMBANGAN MODEL SISTEM INFORMASI PENILAIAN KINERJA RUMAH SAKIT - Fathoni Fathoni; Inda Kesuma S (Jurusan Teknik Informatika, 2011)
The increasing of the competition at health and hospital service as well as society awareness on their rights in health makes the quality of the hospital service need to be concerned. The assesement on hopital service is the basic plan for the betterment and improvement of the hospital quality. In relation to this, a model of information system of hospital service assessment is needed as the initiation of the quality improvement activity. This research was conducted to develop a system information model which can be used to assess the hospital service. In order to achive this goal; the researcher used a model of waterfall system development method and supportive tool through proccess model approach. This research offered an integrated system information model into supportive software that can be used to meassure the hospital work service.